Small angle X-ray scattering study of structural changes in silica gel modified with organofunctional groups - Vollet, Dimas R. [UNESP]; Moreira, José C. [UNESP]; Kubota, Lauro T. [UNESP]; Varela, José Arana [UNESP]; Gushikem, Yoshitaka (Elsevier, 1989)
Silica gel surfaces, organofunctionalized with 2-mercaptobenzimidazole, iminosalicylaldehyde and imidazole groups were examined using the small angle X-ray scattering technique (SAXS). From the scattering intensity data it was concluded that particles have a uniform size after the coupling reaction. The chemical treatment of the silica gel leads to an attachment of the organofunctional groups on the solid-pore interface of the silica with an increase of the mean size of the solid phase and some coalescence of the pores. © 1989.
Keywords: Surfaces--X-Ray Analysis; X-rays--Scattering; Iminosalicylaldehyde Group; Mercaptobenzimidazole Group; Organofunctional Groups; Silica Gel